Voiced and unvoiced separation in malay speech using zero crossing rate and energy - Rafizah Mohd Hanifa; Khalid Isa; Shamsul Mohamad; Shaharil Mohd Shah; Shelena Soosay Nathan; Rosni Ramle; Mazniha Berahim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper contributes to the literature on voice-recognition in the context of non-English language. Specifically, it aims to validate the techniques used to present the basic characteristics of speech, viz. voiced and unvoiced, that need to be evaluated when analysing speech signals. Zero Crossing Rate (ZCR) and Short Time Energy (STE) are used in this paper to perform signal pre-processing of continuous Malay speech to separate the voiced and unvoiced parts. The study is based on non-real time data which was developed from a collection of audio speeches. The signal is assessed using ZCR and STE for comparison purposes. The results revealed that ZCR are low for voiced part and high for unvoiced part whereas the STE is high for voiced part and low for unvoiced part. Thus, these two techniques can be used effectively for separating voiced and unvoiced for continuous Malay speech.